A nanostructure ion-imprinted polymer for the selective separation and determination of copper ions in aqueous solutions. Issue 44 (19th September 2016) - Ashouri, Nasim; Mohammadi, Ali; Shekarchi, Maryam; Hajiaghaee, Reza; Adib, Noushin; Akbari-Adergani, Behrouz
Abstract: A new nanostructure Cu(II) ion-imprinted polymer (IIP) has been prepared using 1-(2-pyridylazo)-2-naphthol as a ligand. The Cu(II)–PAN complex was synthesized and polymerized in the presence of 2-vinylpyridine (the functional monomer), ethylene glycol dimethacrylate (the cross-linker) and 2, 2′-azobisisobutyronitrile (the initiator) via precipitation polymerization using trapping method. The prepared IIP was characterized by FTIR spectroscopy, scanning electron microscopy, and transmission electron microscopy. The optimal pH value for the quantitative preconcentration was 6.0 and maximum sorbent capacity was 11.53 mg g −1 . Under the optimized conditions, the method had a linear analytical range from 1 to 50 μg L −1 . The detection limit, relative standard deviation, and recovery of the method were evaluated as 0.29 μg L −1, 3.6, and 94–97%, respectively. The developed method was successfully applied to the selective extraction and determination of trace amount of copper ions in water samples and some medicinal plants by inductively coupled plasma-optical emission spectrometry.